2017
DOI: 10.1021/acsnano.7b00457
|View full text |Cite
|
Sign up to set email alerts
|

Designing Morphology in Epitaxial Silicon Nanowires: The Role of Gold, Surface Chemistry, and Phosphorus Doping

Abstract: Vertically aligned semiconductor nanowires (NWs) have many potential applications for NW-based technologies, ranging from solar cells to intracellular sensors. Aligned NWs can be fabricated by top-down etching of planar wafers or synthesized from the bottom up using the vapor-liquid-solid (VLS) mechanism to induce epitaxial growth on lattice-matched substrates. The VLS process permits the modulation of dopants along the NW growth axis, which if combined with dopant-dependent wet-chemical etching, can be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 49 publications
3
62
0
Order By: Relevance
“…Even if Au atoms were deposited over the sidewall during the synthesis, they tended to quickly de-wet and form nanoparticle aggregates 11 . Finally, phosphorus, as decomposed from phosphine (PH 3 , an n -type dopant precursor), is known to interact strongly with both Si and Au 16 , 33 , 42 and preferentially accumulate around the nanowire surfaces in n -type Si nanowires 43 . Indeed, previous results on n -type silicon spicules indicate minimum gold-based gradient along Si nanowire sidewalls 11 , confirming the immobilization role of phosphorus over Au.…”
Section: Resultsmentioning
confidence: 99%
“…Even if Au atoms were deposited over the sidewall during the synthesis, they tended to quickly de-wet and form nanoparticle aggregates 11 . Finally, phosphorus, as decomposed from phosphine (PH 3 , an n -type dopant precursor), is known to interact strongly with both Si and Au 16 , 33 , 42 and preferentially accumulate around the nanowire surfaces in n -type Si nanowires 43 . Indeed, previous results on n -type silicon spicules indicate minimum gold-based gradient along Si nanowire sidewalls 11 , confirming the immobilization role of phosphorus over Au.…”
Section: Resultsmentioning
confidence: 99%
“…The bottom-up growth of semiconductor nanowires through the vapor-liquid-solid (VLS) mechanism offers exquisite control over nanowire structure and composition, 1-2 and thus functionality. [2][3][4][5][6] Demonstrations of prototype transistors, 7-10 photodetectors, [11][12][13] solar cells, [14][15][16][17] and biosensors [18][19][20][21] , for example, highlight the promise of these materials for electronic, photonic, energy conversion, and medical applications. However, it remains difficult to produce nanowires in large quantities, especially those with the nanoscale compositional complexity required for the above applications.…”
Section: Introductionmentioning
confidence: 99%
“…Three dimensional (3D) silicon micro-and nanomachining has attracted a lot of interest in recent years for both research and industrial uses, and several promising applications have been proposed and demonstrated, e.g. vertically stacked silicon nanowires for field effect transistors (FET) [1], unified memory [2] and biosensors [3], shape-modified silicon nanopillars for quantum transport study [4] and FET [5], 3D silicon single cubic structures for 3D photonic crystal structures [6], etc. However, to easily fabricate 3D micro-and nanostructures, and simultaneously obtain a good size and shape control of the fabricated structures, is still considered to be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Bottom-up methods can create single crystalline silicon nanostructures, and the morphology can be encoded [6], however, this method is difficult to be integrated in traditional complementary metal-oxide-semiconductor (CMOS) industries. Top-down approaches, which can transfer the 2D lithography patterns into silicon in a 3D structure have been studied extensively before, e.g.…”
Section: Introductionmentioning
confidence: 99%